Peningkatan Perekonomian Kelompok Wanita Kelurahan Tanjung Selamat Kabupaten Deli Serdang Melalui Pengembangan Produk Berbahan Dasar Ikan - Afriani, Dwi Tika; Syafitri, Emmy; Amalia, Mekar Meilisa (Universitas Nusantara PGRI Kediri, 2019)
Community partnership program in Tanjung Selamat Village, Deli Serdang Regency, North Sumatra is motivated by the economic life of some housewives which are in the middle to lower class of economic life. The purpose of this training is to help the problems from the partnership through improving the economic life and family standard living by making a fish sauce. The methods of activities carried out to achieve the objectives of community partnership are: (1) lecture method; (2) discussion method, and (3) practical demonstration method. The practical demonstration method is carried out by training all service participants through the practice of making fish sauce directly to the group of housewives. The results of the activities that have been carried out are the increase in knowledge and skills of housewives in the diversification of processing fisheries food so that they are expected to contribute to improving the family economy.